Gender Equality in Women's Leadership Through The Perspective of The Qur'an and Sayyidah Aisyah Radhiyallahu'Anha - Lilik Huriyah; Yeni Endiana; Yuni Setya Ningsih; Lum’atul Hajar; Afra Nafisah (An-Nisa' Journal of Gender Studies, 2023)
Gender equality which is implemented correctly can have positive impacts on all social aspects. As in the case of aspects of women's leadership that need to be respected without any discrimination. The aim of this research focuses on how to understand gender equality and women's leadership through the perspective of the Qur’an and Sayyidah Aisyah Radhiyallahu'Anha that can be applied to fulfill society's understanding regarding all issues in the aspect of gender equality. The research method used in this research is a qualitative descriptive method with data collection techniques through literature study by collecting relevant data from books, journals, etc. without having to conduct field reviews. The research results that contain the concept of gender equality and women's leadership from the perspective of the Qur’an, are explained in several surahs; some of them are Surah An-Nisa:124, An-Nahl:97, Al-Hujurat:13, An-Naml:23-44, Al-Furqan:74 and also understanding the leadership of Sayyidah Aisyah Radhiyallau'Anha; such as her leadership of the Jamal war, as well as the military. She was also involved in politics and most importantly she was a defender of women. Viewed from these two perspectives, it proves that Islam recognizes gender equality. Men and women have the same right to be leaders.